The responsibility to protect : ending mass atrocity crimes once and for all - Evans, Gareth J., 1944- (Brookings Institution Press, 2008)
"Explains Responsibility to Protect (R2P), a new international norm to protect the peoples of the world. With real-world examples, current events analysis, and assessments from personal experience, shows how R2P is better equipped to end mass atrocity crimes than is "the right to intervene" or other "humanitarian intervention" doctrines"--Provided by publisher.